2013
DOI: 10.1038/ajg.2012.343
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Readmissions in Patients With Inflammatory Bowel Disease

Abstract: Predicting readmission is complex. A predictive model developed to be used at discharge yielded an area under the curve of 0.757.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 19 publications
1
36
2
Order By: Relevance
“…This study found that reasons for 30-day readmission were related to documented flare, infections, or need for pain control. 17 Our study corroborates these previous data. In our cohort, patients with IBD readmitted within 90 days of an index IBD admission were more likely to have underlying depression or chronic pain regardless of the reason for readmission, as opposed to disease type, recent steroid use, or biological use.…”
Section: Discussionsupporting
confidence: 93%
“…This study found that reasons for 30-day readmission were related to documented flare, infections, or need for pain control. 17 Our study corroborates these previous data. In our cohort, patients with IBD readmitted within 90 days of an index IBD admission were more likely to have underlying depression or chronic pain regardless of the reason for readmission, as opposed to disease type, recent steroid use, or biological use.…”
Section: Discussionsupporting
confidence: 93%
“…Early predictive models of readmissions focused on all-cause readmission and the most common diagnoses including congestive heart failure (CHF), acute myocardial infarction (acute MI), and chronic obstructive pulmonary disease (COPD), but the literature now spans multiple diagnoses and disciplines. [515] However, no studies have studied systematically the effects of changing readmission diagnoses being modeled while holding all else equal. This latter understanding will help interpret and compare studies of different diseases.…”
Section: Introduction1mentioning
confidence: 99%
“…These novel observations add to the literature regarding readmission risk factors previously established for other common gastrointestinal conditions, such as inflammatory bowel disease and acute pancreatitis. 14,15 Future study is necessary to design strategies to mitigate early readmission and rebleeding risk, as have been undertaken in other fields. 1619 Given that common causes of hospital readmission and death in the present cohort of patients with LGIB included infection, volume overload, renal failure, and thromboembolic events, potential strategies to mitigate readmission risk could include aggressive monitoring of volume status and infection control as an outpatient, as well as ensuring that patients are restarted on antiplatelets and anticoagulants when possible to decrease postbleeding thrombotic events.…”
Section: Discussionmentioning
confidence: 99%